Physiology of the heart - Katz, Arnold M. (Wolters Kluwer Health/Lippincott Williams & Wilkins Health, 2011)
"Dr. Arnold Katz's internationally acclaimed classic is now in its thoroughly revised Fifth Edition, incorporating the latest molecular biology research and extensively exploring the clinical applications of these findings. In the single authored, expert voice that is this book's unique strength, Dr. Katz provides a comprehensive overview of the physiological and biophysical basis of cardiac function, beginning with structure and proceeding to biochemistry, biophysics, and pathophysiology in arrhythmias, ischemia, and heart failure. Emphasis is on the interrelationships of basic processes among the cell, cardiac muscle function, and the biophysics of contractile and electrical behavior. This edition includes new material on cell signaling and molecular biology"--Provided by publisher.